The role of interictal epileptiform discharges in epilepsy surgery outcome - Jafar Mehvari Habibabadi (International Journal of Preventive Medicine, 2019)
Background: Epilepsy surgery is a fundamental treatment in refractory epilepsy. Video electroencephalographic (v-EEG) monitoring plays an essential role in presurgical evaluation of patients. However there are reports of favorable outcome based on interictal and magnetic resonance imaging (MRI) findings without any need for v-EEG monitoring in patients with temporal lobe epilepsy (TLE). This study aimed to investigate the prognostic effect of concordance between interictal findings and ictal and MRI data on postsurgical outcome of TLE and extratemporal lobe epilepsy (ETLE). Methods: A retrospective study was conducted on 199 patients with refractory focal epilepsy who were admitted for presurgical evaluation. The concordance between irritative zone (IZ) and seizure onset zone (SOZ) and also IZ and MRI lesion was registered, and subsequently the prognostic effect of relevancy on 1-year follow-up result based on Engel criteria was investigated. Results: In TLE and ETLE regarding relevancy between IZ and SOZ, 77.8% and 73.2% were concordant, 2.5% and 0% were discordant, and 19.6% and 26.8% had overlap, respectively. Concordance between IZ and MRI lesion was found in 76.6% and 51.2% of patients with TLE and ETLE while discordance was recorded in 2.5% and 12.2% and overlap registered in 20.9% and 36.6%, respectively. The concordance of interictal findings had no effect on postsurgical outcome of patients with TLE and ETLE. Conclusions: Our study showed that concordance of IZ with SOZ and MRI has no independent effect on postsurgical outcome of patients with TLE and ETLE. We suggest that excluding exceptional cases, v-EEG monitoring should be considered as the mainstay of presurgical evaluation.